Overview of Parental Bonding with Adolescent Mental Health in Bukittinggi 2023 - Wati, Del Fatma; Dewi, Ratna; Permatasari, Debi (PT. Riset Press International, 2024)
Parental bonding is a bonding relationship between parents, both physically and emotionally, that helps shape emotions during the long-term growth and development of adolescents. Generally, parental bonding often refers to an imbalance between care and protection directed by parents toward their children. If it is associated with health conditions such as mental illness, strong parental bonding will affect positive behavior and good and healthy relationships. And if left unchecked, parents will find it difficult to control their children. Adolescents tend to report their feelings to friends when they have problems, such as feeling unwelcome; parents never understand; children don't pay attention to children; parents enter children's privacy spaces; and parents control everything their children do.